MODEL PEMBELAJARAN THINK PAIR SHARE: UPAYA MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SISWA SMP NEGERI 53 MUARO JAMBI - Tiara Dewi Cahyani; Yudi Kurniawan (Jurnal Manajemen Pendidikan, 2026)
This research was motivated by the low interest and cognitive learning outcomes of eighth-grade students in Islamic Religious Education (PAI) at SMP Negeri 53 Muaro Jambi, which was caused by the learning process that was still conventional and teacher-centered. This study aimed to determine whether there was a significant influence of implementing the Think-Pair-Share (TPS) cooperative learning model on students' learning outcomes in the material "Becoming a Tolerant Generation Among Religious Communities." The research method used was a quantitative method with a One Group Pretest-Posttest Experimental Design. The population in this study also served as the research sample (saturated sampling), consisting of all 20 eighth-grade students at SMP Negeri 53 Muaro JambiData analysis techniques included normality tests, hypothesis testing via Paired Sample t-Test, and effectiveness coefficient testing using the N-Gain Score. The results showed that the implementation of the Think-Pair-Share (TPS) cooperative learning model was proven effective in improving student learning outcomes. This was indicated by a significant increase in the class average score from 66.75 during the pre-test to 79.25 during the post-test. Based on the Paired Sample t-Test, a significance value (p-value) of 0.001 was obtained, which is smaller than the significance level of 0.05 (0.001 < 0.05), thereby rejecting Hₒ and accepting Hₐ. The N-Gain Score calculation yielded an average value of 0.3915, indicating that the effectiveness level of the improvement in learning outcomes was in the medium category.